Rasch Model for Validation a User Acceptance Instrument for Evaluating E-learning System - Rachman, Taufiq; Napitupulu, Darmawan Baginda (Bina Nusantara University, 2017)
Advances in science and technology, especially Information and Communication Technology (ICT), has great impacts on the present education management.It allows the development of the e-learning system to facilitate the teaching and learning processes. As a result, many modern universities have developed and utilized the system. For that reason, there is a great need to develop an instrument in which the elearning management system can be evaluated from various aspects such as the system performance, user acceptance, and utilization. The level of the user acceptance is the central focus of this study, known to be strongly related to the level of utilization, and is widely studied by using the famous framework of Davis’ Technology Acceptance Model (TAM). The framework is also adopted in the current study and the required data to analyze quantitatively the model are selectively obtained from a sample of 73 respondents. The validity and reliability of the data are evaluated by using the Rasch model. The results suggest that the all 16 items in the questionnaire are valid and reliable to measure the acceptance of thee-learning system.